The dynamics of firm growth, size and liquidity constraints for Botswana listed firms - Strike Mbulawa; Francis Ogbenna (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
The study employed panel Ordinary Least Squares (OLS) model and panel Vector Autoregressive (VAR) model to examine the dynamic linkages among firm growth, liquidity and firm size. Specifically the study sought to: examine the key variables explaining the growth of firms in an emerging market; examine the reaction of one variable to innovations in another variable within the system and to identify the major drivers of changes in the main variable and the magnitude of the total effect over a certain period of time. Findings, using both panel VAR and panel OLS, showed that growth of firms is financially constrained by the availability of cash flows. There is a significant relationship between cash flows and firm growth which is consistent with theoretical prediction of imperfect capital markets. The panel VAR analysis further that the presence of financial constraints is sensitive to the measure of firm growth. The study shows the existence of causal relationship among firm size, liquidity and growth. Firm size, depending on measure adopted, is affected by availability of cash flows. Variations in investment expenditure were the main drivers of changes in firm growth, firm size and liquidity. The study suggests the need to improve and have a diversified access to finance. Policy makers should aim to develop the financial sector to guarantee sustainable access to bank and stock market finance. The development of strong institutions and reduction of information asymmetry is highly recommended.